The receptor for hyaluronan-mediated motility (RHAMM) expression in neonatal bronchiolar epithelium correlates negatively with lung air content. (December 2018) - Markasz, Laszlo; Savani, Rashmin C.; Sedin, Gunnar; Sindelar, Richard
Abstract: Introduction: Hyaluronan (HA) and the receptor for hyaluronan-mediated motility (RHAMM) may play an important role in lung development. We examined the expression of HA content and RHAMM during postnatal lung development by analyzing human lung specimens from newborn infants with a variety of lung diseases at different gestational (GA) and postnatal (PNA) ages. Materials and methods: Ninety-four patients were evaluated. Immunohistochemical RHAMM expression was studied with digital image analysis, followed by hierarchical cluster analysis of both these data and clinical data to define subgroups. The air content of the lung was determined by computerized analysis. HA content was estimated by radiometric assay. Results: Cluster analysis defined six distinct patient groups (Group 1-2: 34-41 weeks GA; Group 3-5: 23-27 weeks GA; Group 6: mixed population). Group 1-5 showed individual patterns in RHAMM expression and HA content (Group 1: high RHAMM/low HA; Group 2: low RHAMM/low HA; Group 3: low RHAMM/low HA; Group 4: low RHAMM/high HA; Group 5: high RHAMM/high HA). HA content decreased with increasing PNA independently of GA. Negative correlation was observed between air content and RHAMM expression in the bronchiolar epithelium irrespective of clustered groups. Lung hypoplasia appeared in two distinctive groups, with significant differences in lung development and RHAMM expression. Conclusions: RHAMM expression may show dynamic changes during pathological processes in the neonatal lung. The distribution of RHAMM in the lung tissue is heterogeneous with a predominance to the bronchiolar epithelium. We found a negative correlation between lung air content and RHAMM expression in bronchiolar epithelium. Highlights: RHAMM expression in the bronchiolar epithelium correlates negatively with the air content in the lung. Cluster analysis was performed combining immuno-histological results with clinical data. A computerized method describes the air content of the lung in standardized paraffin inflation fixed lung sections. The patients could be sorted into groups by hierarchical clustering.